Evaluation of Teacher Performance Programs in Learning Quality Arabic Language at Bakti Ilaahi Quran Elementary School in Bengkulu City - Nugraha, Hilman; Firmansyah, Leppe (Al-Khair Journal: Management Education, 2025)
Abstrac: The quality of Arabic language learning is still weak, as indicated by many students struggling in practicing daily conversations. This study aims to evaluate the teacher performance program in improving the quality of Arabic language learning at the Quran Elementary School Bakti Ilaahi Bengkulu. It uses a qualitative method with the CIPP evaluation model approach. Data collection techniques were conducted through observation, interviews, and documentation. The evaluation results show that, in general, teachers have prepared learning planning programs in accordance with the applicable curriculum. In terms of teacher performance program input, there are still teachers teaching subjects outside their areas of expertise, such as Arabic being taught by teachers who are not Arabic teachers. The Arabic learning process has been carried out according to the latest curriculum and the established schedule, and in terms of program output, teachers have created performance programs, and students have begun to confidently use the mufrodat (vocabulary) that has been taught, even if only in fragments. Students are able to construct simple sentences in everyday conversations. Thus, it can be concluded that the evaluation results indicate that the teacher performance program can improve the quality of Arabic learning in the school. Therefore, it is recommended that to further improve the quality of Arabic learning, the evaluation of the teacher performance program in the school should be strengthened. Keywords: Evaluation, Teacher Performance Program, Quality of Arabic Language Learning. Abstrak: Mutu pembelajaran Bahasa Arab masih lemah, ditandai banyak anak lemah dalam praktek percakapan keseharian. Penelitian ini bertujuan untuk mengevaluasi program kinerja guru dalam mutu pembelajaran Bahasa Arab di Sekolah Dasar Quran Bakti Ilaahi Bengkulu. Menggunakan metode kualitatif dengan pendekatan model evaluasi CIPP. Teknik pengumpulan data dilakukan melalui observasi, wawancara, dan dokumentasi. Hasil evaluasi menunjukkan bahwa secara umum guru telah menyusun program perencanaan pembelajaran sesuai dengan kurikulum yang berlaku. Input program kinerja guru, masih ada guru mengajar tidak sesuai bidang keahliannya seperti masih ada guru mengajar Bahasa Arab oleh non guru Bahasa Arab. Proses pembelajaran Bahasa Arab telah dilaksanakan sesuai kurikulum terkini dan sesuai jadwal yang telah ditentukan, dan pada produk program guru telah membuat program kinerja, dan siswa sudah berani menggunakan mufrodat yang sudah di ajarkan walaupun sepotong-potong kata, siswa mampu merangkai kalimat sederhana dalam percakapan sehari-hari. Dengan demikian dapat disimpulkan bahwa hasil evaluasi menunjukkan bahwa program kinerja guru dapat meningkatkan utu pembelajaran Bahasa Arab di sekolah. Sehingga dapat disarankan untuk meningkatkan mutu pembelajaran Bahasa Arab, maka tingkatkan evaluasi program kinerja guru di sekolah.Kata Kunci: Evaluasi, Program Kinerja Guru, Mutu Pembelajaran Bahasa Arab.